2016
DOI: 10.1212/wnl.0000000000003035
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment, behavioral impairment, depression, and wish to die in an ALS cohort

Abstract: Objective: To evaluate relationships among cognitive, behavioral, and psychiatric/psychosocial measures assessed in a multicenter cohort of patients with amyotrophic lateral sclerosis (ALS). Methods:Recently diagnosed patients with definite or probable ALS diagnosis were administered 7 standardized psychiatric/psychosocial measures, including the Patient Health Questionnaire for diagnosis of depression and elicitation of wish to die. The Cognitive Behavioral Screen was used to classify both cognitive and behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 36 publications
1
39
2
3
Order By: Relevance
“…Rabkin et al [222] clearly indicated that the degree of depression and the wish to die are directly dependent upon the presence or absence, and severity of behavioural and cognitive impairment of the patients [222]. Therefore, patients exhibiting early symptoms of ALS must be screened for dementia and depression for designing proper treatment regime.…”
Section: Amyotrophic Lateral Sclerosis and Related Psycho-behaviouralmentioning
confidence: 99%
See 1 more Smart Citation
“…Rabkin et al [222] clearly indicated that the degree of depression and the wish to die are directly dependent upon the presence or absence, and severity of behavioural and cognitive impairment of the patients [222]. Therefore, patients exhibiting early symptoms of ALS must be screened for dementia and depression for designing proper treatment regime.…”
Section: Amyotrophic Lateral Sclerosis and Related Psycho-behaviouralmentioning
confidence: 99%
“…Clinical studies on BD subjects revealed that only 48% chances of complete recovery with 24% chances of functional restoration are possible [228,230]. Studies also indicated that the after effects of manic episodes can be witnessed even at workplace, home and surroundings even after five years [222]. Elevated creativity and productivity was also observed in several BD patients.…”
Section: Bipolar Disorder and Related Psychobehavioural Anomaliesmentioning
confidence: 99%
“…Contrary to what was believed in the past, ALS is not only a motor disorder. Indeed, more than 50% of patients also have cognitive dysfunctions over the disease course, in terms of changes in executive and language functions, behavior, social cognition, memory, and sometimes with the appearance of neuropsychiatric symptoms . According to the literature, roughly 30%‐40% of patients have only cognitive impairment, 10% have only behavioral impairment, and 15%‐20% show clear frontotemporal dementia (FTD), according to the revised diagnostic criteria by Strong .…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that patients with ALS have a prevalence of depressive disorders higher than healthy subjects, but lower than patients with a variety of other medical and neurological conditions, such as multiple sclerosis, Parkinson's disease, and Alzheimer's disease . The percentage of mood disorders in ALS is variable in different studies, from about 10%‐30%, depending on differing measurements of depression (both in terms of semi‐structured interview and in terms of self‐reported scales, eg, Structured Clinical Interview for DSM‐5, Patient Health Questionnaire, ALS Depression Inventory). However, major depression is uncommon .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation